Effect of foremilk and hindmilk on simple procedural pain in newborns - SAVE, DİLŞAD; ÖZEK, EREN; BİLGEN, HÜLYA SELVA (WILEY, 2005)
Background: Infants are exposed to painful stimuli during routine medical care in the first few days of life. The aim of the present study was to compare the effect of foremilk; hindmilk, which has been known to have more fat content than foremilk; and sterile water in reducing pain in newborns undergoing minor painful procedures. Methods: Sixty-two healthy term infants requiring a heel prick blood sample for screening tests were randomly allocated to receive 2 mL of foremilk, hindmilk or sterile water. Median crying time, duration of the first cry, percent change in heart rate, maximum heart rate and neonatal facial coding system scores were recorded to assess the infants' response to pain. Results: Statistically significant differences between the three groups were not found in terms of crying time, duration of the first cry, percent change in heart rate or maximum heart rate (P = 0.19, P = 0.08, P = 0.22 and P = 0.91, respectively). When the mean pain scores of the groups were compared at 0, 1, 2 and 3 min, there was no statistically significant difference between the three groups (P = 0.58, P = 0.55, P = 0.58 and P = 0.84 for 0, 1, 2 and 3 min, respectively). Conclusion: Although hindmilk has a minor superiority in terms of crying time, duration of the first cry and percent change in heart rate, it does not reach statistical significance. It is concluded that neither foremilk nor hindmilk is superior in relieving pain when compared to placebo.
Keywords: analgesia; foremilk; hindmilk; neonate; HUMAN-MILK; 10-DAY-OLD RATS; HEALTHY NEWBORNS; INFANTS; SUCROSE; CHILDREN; EXPRESSION; ANALGESIA; GLUCOSE; HYPOALGESIA